2009
DOI: 10.1161/circulationaha.108.841445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Aortic Insufficiency on Outcome After Aortic Valve–Sparing Surgery

Abstract: Background-The presence of significant preoperative aortic insufficiency (AI) or the need for cusp repair has been suggested as a risk factor for poorer outcomes after aortic valve (AV)-sparing surgery. We analyzed the influence of these factors on the mid-term outcomes of AV surgery. Methods and Results-Between 1996 and 2008, 164 consecutive patients underwent elective AV-sparing surgery. Severe preoperative AI (grade Ն3ϩ) was present in 93 patients (57%), and 54 (33%) had a bicuspid valve. Root repair was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 20 publications
6
33
1
Order By: Relevance
“…If the valve cusps showed minor pathologies with basically good quality of tissue, then further cusp repair was performed, such as plication of the central portion [8] (Fig. 1C), elevation of the commissures or decalcification [9] (Fig. 1D).…”
Section: Surgical Techniquementioning
confidence: 99%
“…If the valve cusps showed minor pathologies with basically good quality of tissue, then further cusp repair was performed, such as plication of the central portion [8] (Fig. 1C), elevation of the commissures or decalcification [9] (Fig. 1D).…”
Section: Surgical Techniquementioning
confidence: 99%
“…This study investigated which clinical settings could influence outcomes in patients with expanded indication for VSRR in order to determine the populations who would benefit from this procedure. Points in controversies on indications for VSRR are different according to the reports in which needs of cusp repair [2], AAAD (3), inherited connective tissue disorder [12,13], cusp anomaly [14], or preoperative severe AR [15] particularly became a major focus. These reports demonstrated that each isolated indication came to favorable results that were equal to those of the control group.…”
Section: Commentmentioning
confidence: 99%
“…The predictors of recurrent AR were preoperative left ventricle end-diastolic diameter and residual AR on discharge echocardiography. 40,41) These results might represent an earlier indication for VSRR and aggressive cusp repair if necessary. Svensson and colleagues used the CLASS (Commissure, Leaflet, Annulus, Sinuses, Sinotubular) evaluation for selecting the appropriate procedure and achieved excellent results after VSRR and concurrent cusp repair.…”
Section: Vsrr Combined With Cusp Repairmentioning
confidence: 76%
“…48) As reimplantation using the Valsalva graft confers the advantages of less cusp stress and secure annular fixation, the reoperation rate should be lower. 31,40) The level of cusp coaptation after reimplantation 44) and residual AR upon discharge 40,41) are possible predictors of recurrent AR. Whether VSRR combined with cusp repair is a risk factor for recurrent AR remains controversial.…”
Section: Predictors Of Recurrent Ar After Vsrrmentioning
confidence: 99%
See 1 more Smart Citation